Determinants of Online Zakat Intention amongst Muslim Millennials: An Integration of Technology Acceptance Model and Theory of Planned Behavior - Ninglasari, Sri Yayu (IAIN Surakarta, 2021)
Today’s modern civilization has resulted in the crucial role of technology in human life, including financial matter. Integrating Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB), this study sheds some light on the determinants of Muslim millennials’ intention in performing zakat payment using Financial Technology (Fintech). An online questionnaire survey was conducted to gather the required data from a group of Indonesian Muslim millennials. Employing purposive sampling technique, the sample consisted of 200 respondents. The data were analyzed with the assistance of Structural Equation Model - Partial Least Square (SEM-PLS). The results demonstrated that perceived ease of use and perceived usefulness positively and significantly affected the respondents’ attitudes. Moreover, attitudes, subjective norms, and perceived behavioral control significantly affected the intention of using Fintech to perform zakat payment. The results further revealed that there was no direct influence between perceived ease of use and perceived usefulness on the respondents’ intention to use Fintech. However, it had an indirect effect by the mediation of attitude variable. As a theoretical implication, this study contributes to the literature enhancement in the discourse of TAM and TPB models in zakat context. Practically, it assists zakat management institutions recognize the Muslim millennial community and develop digital zakat payment platforms.